Analysis of the Budgeting System: A Case Study of a Manufacturing Company - Bybordi, Nazanin; Ousama, A. A.; Shreim, Obeid S. (Asian Journal of Accounting Perspectives, 2019)
Research aim: This paper aims to analyse the practice of the budgeting system in a light manufacturing company operating within the Iranian automotive industry. Design/ Methodology/ Approach: The paper uses a case study method based on a lighting manufacturing company. A semi-structured interview was implemented to collect the required data. The respondents consist of a total of four department managers and the Chief Executive Officer (CEO) of the company. Research finding: The paper found that the current system being used for budgeting is not efficient due to the significant variances between actual figures (performance) and planned budget. Theoretical contribution/ Originality: This paper is considered among the empirical studies to evaluate the budgeting system applied to a manufacturing company within the Iranian automotive industry. Practitioner/ Policy implication: The paper reveals important weaknesses in the budgeting system practised in Iran. This finding can be considered very useful as it highlights that the system suffers from inefficiency. Companies can attempt to improve the system by implementing effective methods such as the formation of a budget committee, and preparation of the cash budget to increase the efficiency of the system. Research limitation/ Implication: Although the paper provides evidence on the status of budgeting systems, it focused predominantly on interviews. Future research on this issue may use data triangulation by using other primary (e.g. questionnaire survey) and secondary data. Keywords: Budgeting System, Budget, Evaluation, Lighting Industry, Iran Type of article: Research paper JEL Classification: M4, M41